Administrative Chairs and Decision Making - Dean J. Laury Ed.D (Academic Chairpersons Conference Proceedings, 2019)
Presenter and participants will discuss decision-making strategies and best practices via case studies available to chairs (new or veterans) to support the decision making process within department operations.
Keywords: Department culture; Decision theory; decision analysis; decision making